Medieval mereology - Henry, Desmond Paul (Bochumer Studien zur Philosophie, 1991)
Mereology is the theory which deals with parts and wholes in the concrete sense, and this study follows its varied fortunes during the Middle Ages. Preliminary indications as to its metaphysical situation are followed by a brief sketch of Boethius' contribution. Peter Abelard, Gilbert of Poitiers, Clarembald of Arras, and Joscelin of Soissons are among the twelfth-century authors examined. The effect of the subsequent recovery of Aristotle's Metaphysica on Mereology is typified by sketches of the many and varied uses made of the latter by Aquinas. A brief sample of Buridanian treatment.